2017
DOI: 10.1186/s13148-017-0380-0
|View full text |Cite
|
Sign up to set email alerts
|

Tri-methylation of H3K79 is decreased in TGF-β1-induced epithelial-to-mesenchymal transition in lung cancer

Abstract: BackgroundThe epithelial-to-mesenchymal transition (EMT) enables epithelial cancer cells to acquire mesenchymal features and contributes to metastasis and resistance to treatment. This process involves epigenetic reprogramming for gene expression. We explored global histone modifications during TGF-β1-induced EMT in two non-small cell lung cancer (NSCLC) cell lines and tested different epigenetic treatment to modulate or partially reverse EMT.ResultsLoss of classical epithelial markers and gain of mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 71 publications
3
32
0
Order By: Relevance
“…For in vitro study, we blocked the expression of DOT1L in GC cells by transfection, and found that the proliferation ability of the cells was significantly decreased. It was previously reported that DOT1L inhibition in ovarian cancer and lung cancer may result in cell cycle G 1 inhibition and the association of DOT1L with DNA replication [12,19]. By examining the cell cycle, we found that the G 1 phase of GC cells was stagnant, thus causing cell proliferation to slow down.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…For in vitro study, we blocked the expression of DOT1L in GC cells by transfection, and found that the proliferation ability of the cells was significantly decreased. It was previously reported that DOT1L inhibition in ovarian cancer and lung cancer may result in cell cycle G 1 inhibition and the association of DOT1L with DNA replication [12,19]. By examining the cell cycle, we found that the G 1 phase of GC cells was stagnant, thus causing cell proliferation to slow down.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, the vital functioning of DOT1L in the mixed lineage leukemia (MLL)-rearranged leukemia has been shown [8], and thus DOT1L-targeted inhibitors have been used in rearranged leukemia [9]. In solid tumors, DOT1L is also involved in its progression, such as breast cancer [10], ovarian cancer [11], and lung cancer [12]. However, to date, the therapeutic value and the prognostic impact of DOT1L in GC has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous reports in the past stating the significance of cadherin switching in progression and malignancy of BCa pointing to the importance of elucidating the mechanism for targeted therapy (32)(33)(34)(35)(36)(37). Moreover, it was already shown that NRP2 and E-Cadherin expression are connected in multiple cancer types (23,(38)(39)(40)(41). However, unlike the positive correlation in our model system, all publications reported a negative correlation.…”
Section: Nrp2 Positively Regulates Osteopontin Expressionmentioning
confidence: 63%
“…BETi can inhibit MYC function and also lead to reduced expression of PD-L1. 44, [71][72][73][74][75] BETi can result in decreased MYC expression but also can block the ability of MYC to mediate gene amplification. 76,77 Therefore, BETi could have influence on MYC function through multiple mechanisms.…”
Section: Myc and Other Oncogenes Regulates Pd-l1mentioning
confidence: 99%
“…75 The BET inhibitor PFI-1 reduced PD-L1 levels in lung cancer. 72 The BETi OTX015 reduces PD-L1 expression in stromal cells. 73 The BETi iBET151 reduces PD-L1 and also inhibits the NF-kB family through inhibitor of kB as well as MYC.…”
Section: Myc and Other Oncogenes Regulates Pd-l1mentioning
confidence: 99%